Myoepithelial cell‐specific expression of stefin A as a suppressor of early breast cancer invasion. Issue 4 (31st October 2017) - Duivenvoorden, Hendrika M; Rautela, Jai; Edgington‐Mitchell, Laura E; Spurling, Alex; Greening, David W; Nowell, Cameron J; Molloy, Timothy J; Robbins, Elizabeth; Brockwell, Natasha K; Lee, Cheok Soon; Chen, Maoshan; Holliday, Anne; et al.
Abstract: Mammography screening has increased the detection of early pre‐invasive breast cancers, termed ductal carcinoma in situ (DCIS), increasing the urgency of identifying molecular regulators of invasion as prognostic markers to predict local relapse. Using the MMTV‐PyMT breast cancer model and pharmacological protease inhibitors, we reveal that cysteine cathepsins have important roles in early‐stage tumorigenesis. To characterize the cell‐specific roles of cathepsins in early invasion, we developed a DCIS‐like model, incorporating an immortalized myoepithelial cell line (N1ME) that restrained tumor cell invasion in 3D culture. Using this model, we identified an important myoepithelial‐specific function of the cysteine cathepsin inhibitor stefin A in suppressing invasion, whereby targeted stefin A loss in N1ME cells blocked myoepithelial‐induced suppression of breast cancer cell invasion. Enhanced invasion observed in 3D cultures with N1ME stefin A‐low cells was reliant on cathepsin B activation, as addition of the small molecule inhibitor CA‐074 rescued the DCIS‐like non‐invasive phenotype. Importantly, we confirmed that stefin A was indeed abundant in myoepithelial cells in breast tissue. Use of a 138‐patient cohort confirmed that myoepithelial stefin A (cystatin A) is abundant in normal breast ducts and low‐grade DCIS but reduced in high‐grade DCIS, supporting myoepithelial stefin A as a candidate marker of lower risk of invasive relapse. We have therefore identified myoepithelial cell stefin A as a suppressor of early tumor invasion and a candidate marker to distinguish patients who are at low risk of developing invasive breast cancer, and can therefore be spared further treatment. Copyright © 2017 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.